The redox budget of crust-derived fluid phases at the slab-mantle interface. (15th July 2017) - Malaspina, N.; Langenhorst, F.; Tumiati, S.; Campione, M.; Frezzotti, M.L.; Poli, S.
Abstract: The redox processes taking place in the portion of the mantle on top of the subducting slab are poorly investigated and the redox potential of crust-derived fluid phases is still poorly constrained. A case study of supra-subduction mantle affected by metasomatism from crust-derived fluid phases is represented by garnet orthopyroxenites from the Maowu Ultramafic Complex (China) deriving from harzburgite precursors metasomatised at ∼4 GPa, 750–800 °C by a silica- and incompatible trace element-rich fluid phase. This metasomatism produced poikilitic orthopyroxene and inclusion-rich garnet porphyroblasts. Solid multiphase primary micro-inclusions in garnet display negative crystal shapes and infilling minerals (spinel, ±orthopyroxene, amphiboles, chlorite, ±talc, ±mica) occur with constant modal proportions, indicating that they derive from trapped solute-rich aqueous fluids. FT-IR hyper spectral imaging analyses and Raman spectroscopy, together with X-ray microtomography performed on single inclusions indicate that liquid water is still preserved at least in some inclusions (±spinel). To investigate the redox budget of these fluid phases, we measured for the first time the Fe 3+ concentration of the micron-sized precipitates of the multiphase inclusions using EELS on a TEM. Results indicate that spinel contains up to 12% of Fe 3+ with respect to the total iron, amphibole about 30%, while the ratio in inclusion phases such as chlorite and phlogopite may reach 70%. The Fe 3+ fraction of the host garnet is equal to that measured in spinel as also confirmed by Flank Method EPMA measurements. Forward modelling f O2 calculations indicate that the garnet orthopyroxenites record ΔFMQ = −1.8 ÷ −1.5, therefore resulting apparently more reduced with respect to metasomatised supra-subduction garnet-peridotites. On the other hand, oxygen mass balance, performed both on the Maowu hybrid orthopyroxenite and on metasomatised supra-subduction garnet peridotites, indicate that the excess of oxygen (nO2 ) is the same (10 mol m −3 ). The oxygen mass balance of the crust-derived fluids (multiphase inclusions) also indicates that the fluid precipitates are more oxidised than the host rock, reaching up to 400 mol m −3 of nO2 . This suggests that even after their interaction with the metasomatic orthopyroxenites, the residual fluid phases could be potentially carrier of oxidised components when it escapes the slab-mantle interface. Because of this gradient in nO2, a metasomatic front develops from the oxidised slab to the overlying lithospheric mantle wedge passing through a transitional layer of hybrid rocks at the slab-mantle interface.